2016
DOI: 10.12659/msm.898727
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated Inguinal Hernia Mesh Repair: Effect on Testicular Blood Flow and Sperm Autoimmunity

Abstract: BackgroundThe aim of our study was to determine an influence of incarcerated inguinal hernia mesh repair on testicular circulation and to investigate consequent sperm autoimmunity as a possible reason for infertility.Material/MethodsThis prospective study was performed over a 3-year period, and 50 male patients were included; 25 of these patients underwent elective open mesh hernia repair (Group I). Group II consisted of 25 patients who had surgery for incarcerated inguinal hernia. Doppler ultrasound evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In addition, in 2016, Krnić et al, 28 prospectively examined 50 men. Twenty‐five of these patients underwent elective open mesh hernia repair (Group I), while group II consisted of 25 patients who had surgery for incarcerated inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in 2016, Krnić et al, 28 prospectively examined 50 men. Twenty‐five of these patients underwent elective open mesh hernia repair (Group I), while group II consisted of 25 patients who had surgery for incarcerated inguinal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…shown that mesh hernia repair without complication cause only a transitory change in testicular blood flow and no clinical significant autoimmune reaction. 27 In addition, in 2016, Krnić et al, 28 prospectively examined 50 men. In the present study, the sample of patients examined is the largest at the best of our knowledge until now reported.…”
Section: Discussionmentioning
confidence: 99%